Composition and Structure of Tree and Sapling Level Plants in Nagari Paru Forest, Sijunjung Regency - Geovana, Savira; Chairul, Chairul; Mukhtar, Erizal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study discusses the composition and structure and estimates the potential carbon reserves and environmental service value of the Nagari Paru Forest (Rimbo Larangan) in Sijunjung Regency, West Sumatra. The method used was the transect method with purposive sampling. The vegetation observed consisted of trees and tree seedlings. The results showed that the tree-level vegetation consisted of 17 families, 21 genera, 23 species, and 53 individuals, with Hopea sangal as the dominant species, while the sapling-level vegetation consisted of 17 families, 23 genera, 24 species, and 94 individuals, dominated by Drepananthus ramuliflorus. The diversity index (H') was moderate, at 2.95 for trees and 2.74 for seedlings. This study shows that the Nagari Paru Forest has great ecological potential and can support climate change mitigation efforts and community empowerment through environmental service schemes.